Bacteriological Profile of Chronic Suppurative Otitis Media and Antibiotic Susceptibility in a Tertiary Care Centre of Central Nepal - Sapkota, Anita; Aryal, Bivek; Bhandari, Ramesh; Lohani, Suman; Saroj Panta, Saroj; Sapkota, Ajeet (Journal of Bharatpur Hospital, 2025)
Background Chronic suppurative otitis media is one of the most common cause of hearing impairment especially in developing countries due to illiteracy, poor hygiene, respiratory infections and poverty. If left unchecked, it can cause serious local and systemic complications. The aim of the study was to determine the causative organisms and their antibiotic susceptiility pattern. Methods This study included total 90 patients who were clinically diagnosed as chronic suppurative otitis media having active ear discharge presenting to outpatient Department of ENT, Bharatpur hospital from May 2024 to Feb 2025.Pus swab was obtained under aseptic precautions and samples were processed in microbiological lab using standard operating protocol. For isolated bacterial strains, antibiotic susceptibility test was performed by using Kirby Bauer disc diffusion method and the results were analyzed using simple statistical techniques. Results The most commonly affected age group was >40 years and majority of them had unilateral disease. Females were more affected than males. The most common isolated organisms were Pseudomonas aeruginosa (47.8%) and Staphylococcus aureus (8.9%) followed by Klebsiella Pneumoniae (7.8%), E. coli (5.6%), Proteusmirabilis (5.6%), Acinetobacter (3.3%), Coagulase negative Staph aureus (2.2%) and proteus vulgaris (1.1%). Majority of the common isolated strains were sensitive to Amikacin and Levofloxacin. Ciprofloxain was found to be one of the least sensitive drugs and majority of strains were found to be resistant to Amoxyclav and third generation cephalosporins. Conclusions Pseudomonas aeruginosa was the most common predominant isolated organism followed by Staphylococcus aureus. It is essential to know the etiological agents of CSOM and their antimicrobial susceptibility for effective treatment and preventing both the complications and development of antibiotic resistance.